Compositional and Isotopic Analytical Methods in Archaeological Micromorphology. Issue 1 (5th December 2012) - Mentzer, Susan M.; Quade, Jay
<x xml:space="preserve">Abstract</x> Resin‐impregnated sediment blocks are a by‐product of micromorphological sample processing. These blocks can be further studied using a variety of destructive, nondestructive, and minimally destructive geochemical techniques. X‐ray fluorescence microanalyses conducted on sediment blocks yield semiquantitative major and trace elemental abundances that can be used to generate compositional maps, and to illustrate compositional change within or between archaeological strata and features. Sediment blocks can also be drilled to obtain small sediment samples for stable oxygen and carbon isotopic analyses. Both elemental and isotopic analyses can be conducted in conjunction with micromorphological analyses to yield a holistic picture of archaeological sediment composition, source, and depositional processes. The integration of micromorphological, compositional, and isotopic analyses is used here to aid in the differentiation of calcareous ash and lime plasters from the Neolithic site of Asıklı Höyük, Turkey.